Optimal generation of mesoscopic twin-beam states by means of a natively femtosecond laser system - A. Pozzoli; M. Lamperti; M. Clerici; M. Bondani; A. Allevi (APL Photonics)
Mesoscopic twin-beam states, which exhibit robust nonclassical correlations, hold significant potential for applications in quantum technologies, including underwater quantum communication and quantum metrology. As Ytterbium-based lasers delivering sub-picosecond pulses are becoming the cornerstone of ultrafast photonics, optimizing the generation of quantum states of light driven by such short pulses while avoiding the presence of noise sources, such as spurious light, is also becoming essential. To this end, we propose an optical scheme that delivers well-populated entangled states in the red spectral region by pumping parametric down-conversion with optically tilted pulses, addressing the limited gain caused by group velocity mismatch between the driving pump field and the generated quantum radiation. The results obtained so far encourage the exploitation of this source in further optical schemes.